019 PP: REPRODUCTION OF THE SOCIOTECHNICAL GAP IN MIXED QUANT/QUAL HEALTH RESEARCH COLLABORATIONS. (3rd March 2017) - Willis, M; Meyer, E
Abstract : In this paper, we report a reflexive case study of collaborative health research. The project we discuss (and are involved in) seeks to understand, evaluate, and eventually identify probabilities for the automation of work tasks in general practice medical services. This project is in two phases. The first is primarily qualitative, and is designed to gather data from observations, interviews, document collection, video, and ethnographic fieldwork in general practice surgeries. The second phase uses these qualitative data to develop models using quantitative data (from surveys and external data sources) that predicts the automation probability of various tasks. This research involves collaboration on multiple fronts: between different academic specializations, among academic researchers and healthcare clinicians and administrative staff, and coordinating academic analysis and technological development. While the only way to really do such a project is via collaboration, each point of collaboration also increases the complexity of the project and adds to the project's requirements. A key tension lies between quantitative engineering development and qualitative empirical research and theoretical development. We suggest this duality can be understood through frameworks from the field of computer supported cooperative work, where it is often discussed as the gap between social requirements and technological feasibility. Our collaboration between qualitative research and technological development embodies the notion that social activity is nuanced and fluid whereas technological development is precise, ridged, and brittle (following Ackerman, 2000). We explore the reproduction of this gap and its impact in sociotechnical research and development collaborations in health research.